Essentials of consensual qualitative research - Clara E Hill; Knox, Sarah (Washington American Psychological Association, 2021)
The brief, practical texts in the Essentials of Qualitative Methods series introduce social science and psychology researchers to key approaches to capturing phenomena not easily measured quantitatively, offering exciting, nimble opportunities to gather in-depth qualitative data.In this volume, Clara E. Hill and Sarah Knox describe consensual qualitative research (CQR), an inductive method characterized by open-ended interview questions, small samples, a reliance on words over numbers, the importance of context, an integration of multiple viewpoints (for example, the consensus of the research team and auditors), and a high emphasis on rigor and replicability. CQR is especially well suited to research that requires rich descriptions of inner experiences, attitudes, and convictions, and is therefore widely used by psychotherapy researchers.
Keywords: Social Sciences